Cultural values and students' intentions of choosing accounting career - Dalci, Ilhan; Ozyapici, Hasan (Emerald Group Publishing Ltd, 2018)
Purpose - This paper aims to explore whether cultural values identified by Hofstede (1980) are relevant with respect to the relationship between career drivers and students' intentions of pursuing a career in accounting. Design/methodology/approach - A total of 266 Turkish, East African, West African, Iranian and Arabic business-related students studying at Eastern Mediterranean University in North Cyprus have participated in this study. To test the hypotheses, a t-statistic at the univariate level and a discriminant analysis at the multivariate level have been performed. Findings - The results reveal that collectivism and/or large power distance are associated with the statistically significant relationship between parental and pews' influence and students' intentions of choosing an accounting career. The results further demonstrate that collectivism and/or strong uncertainty avoidance is/are relevant to insignificant relationship between beliefs factors and students' career aspirations into accounting profession. Research limitations/implications - The main implication derived from this study states that the accounting educators and professional accounting firms should mostly target parents and convince them of the positive aspects of accounting study and profession to attract more students from cultures characterized by collotiv ism and large power distance. Parallel to this, the results suggest that mil:a skits and professional accounting firms should use their current students to attract more students into their accounting-related programs. Practical implications - Given evidence that cost of education is an important issue for the students opting to pursue a career in accounting, educators could attract more students into their accounting programs by providing scholarships to bright students intending to study accounting. They could also increase attractiveness by offering reductions in tuition fees to the students for obtaining good grades in accounting courses. Originality/value - This study is unique in the sense that it takes a new step to investigate the influence of career-choice factors by using multiple dimensions of cultural values. in addition, this could be the first study exploring the factors that may influence decision of the students studying in North Cyprus in choosing accounting career.
Keywords: Accounting education; Culture; Accounting career; Career drivers